An experimental–numerical investigation of hydrothermal response in adhesively bonded composite structures. (June 2015) - Sarfaraz, Roohollah; Canal, Luis P.; Violakis, Georgios; Botsis, John; Michaud, Véronique; Limberger, Hans G.
Abstract: Water absorption and thermal response of adhesive composite joints were investigated by measurements and numerical simulations. Water diffusivity, saturation, swelling, and thermal expansion of the constituent materials and the joint were obtained from gravimetric experiments and strain measurements using embedded fiber Bragg grating (FBG) sensors. The mechanical response of these materials at different temperatures and water content was characterized by dynamic mechanical analysis. Thermal loading and water absorption in joint specimens were detected by monitoring the FBG wavelength shift caused by thermal expansion or water swelling. The measured parameters were used in finite element models to simulate the response of the embedded sensor. The good correlation of experimental data and simulations confirmed that the change in FBG wavelength could be accurately related to the thermal load or water absorption process. The suitability of the embedded FBG sensors for monitoring of water uptake in adhesive composite joints was demonstrated.